Pencarian Rute Terdekat Lokasi Evakuasi Tsunami Dengan Metode Pencarian Dijkstra Dan Pendekatan MADM - Syahputra, M Ramdhan; Asriyanik, Asriyanik (LPPM UNIKA Santo Thomas Medan, 2023)
Tsunami is one of the natural disasters that threatens Indonesia, where one of the major factors is caused by an earthquake that occurred on the seabed and has been recorded to have claimed many lives. Behind this incident, there are problems faced by the society when evacuating themselves, one of which is the ignorance of access to evacuation routes, so that people fail to take advantage of their time to evacuate. In this study applying Dijkstra method with SAW and Haversine approaches at Pelabuhan Ratu, Sukabumi Regency, the final weight results are grouped based on 3 main parameters, namely road width, distance traveled and estimated arrival time, also at the end of this study resulted in an Android application that implements the model that has been created.